Policy and programme implementation and the productivity and impact of new secondary schools in Jamaica - Clarke, Velta Joy (1986)
This study evaluates the policy and programme implemented in the new secondary schools that were introduced in Jamaica in 1974, through an analysis of the productivity, and socio-economic and socio-political impact of the schools. The main issues derive from the interplay of forces infringing on the policy: 1) there are evident contradictions between the double track educational system and the social goal of equality--there are differences of student selection programmes, teacher qualifications, examinations, financing, and facilities between the prestigious high schools and low-status new secondary schools; 2) policy aims and the rate of growth of the economy show dynamic interdependence; and 3) students have inescapable socio-economic problems. The results of the study indicate that the productivity of new secondary schools is low, in that only a small percentage of students perform satisfactorily on the SSC examinations. There is also minimal impact on higher education, unemployment, and equality of educational outcomes. In essence, the productivity and impact of new secondary schools are so inextricably linked with powerful socio-economic, political, and institutional antecedents, that the goals and operations of the programme in its present form are not seen to be effective, efficient, or significant as an instrument of policy. The system needs to be reformed
Keywords: School effectiveness